Relationships between Impulsivity and Subjective Response in an IV Ethanol Paradigm - Leeman, Robert F. (2014)
RATIONALE: Impulsivity and individual differences in subjective response to alcohol are risk factors for alcohol problems and possibly endophenotypes for alcohol dependence. Few prior studies have addressed relationships between the two constructs. OBJECTIVES: To predict subjective responses to ethanol, we tested self-reported impulsiveness, ethanol dose condition (high dose, low dose or placebo) and time (7 timepoints) along with interactions among these variables. METHODS: The present study is a secondary analysis of data from a within subject, placebo-controlled, dose-ranging ethanol administration study using IV infusion with a clamping technique to maintain steady-state breath alcohol concentration. The sample consisted of healthy, non-alcohol dependent social alcohol drinkers between the ages of 21-30 (N=105). Participants at varying levels of impulsivity were compared with regard to stimulant and subjective responses to three ethanol dose conditions over time. RESULTS: Individuals with higher impulsivity reported stronger stimulant and weaker sedative response to alcohol, particularly at the higher dose. Higher impulsivity was associated with a steeper increase in stimulant effects during the first half of clamped ethanol infusion with the higher dose. CONCLUSIONS: These results suggest that impulsive individuals may experience enhanced reinforcing, stimulant effects and relatively muted aversive, sedative effects from alcohol. These subjective responses may relate to enhanced risk of alcohol problems among more impulsive individuals.